Understanding pension saving among the self-employed - Jonathan Cribb; Heidi Karjalainen (Institute for Fiscal Studies (IFS), 2023)
Private pension saving among the self-employed population in the UK has been falling dramatically over the last few decades, and this has led to a heightened policy focus on how to boost pension saving among this group. In this report we analyse patterns of private pension saving among the self-employed using administrative tax data. We focus on a specific group of the self-employed - those who are working-age (age 22-64), long-term self-employed (self-employed for at least five consecutive years) and have no income from a job as an employee.
Keywords: 330; Employment and income; Savings; pensions and wealth; Ageing; Private pensions; Retirement; Employment; Savings; Tax